Use of industrial waste-based zeolites in the fabrication of cementitious materials - J.L. García Calvo; P. Carballosa; I. Padilla; R. Jarabo; M. Romero; A.. López-Delgado (Materiales de Construccion)
Two types of zeolites, coming from the total conversion of hazardous aluminum waste, have been considered in this study: NaP-type zeolite and LTA-type zeolite. Both zeolites are proposed to be used in cementitious mortars by substituting cement content in 5, 10 and 15%. The microstructure of both zeolites was characterized and they have certain interesting characteristics to be used as supplementary cementitious materials. The main fresh state characteristics and the mechanical performance of the fabricated mortars were also evaluated. The lower particle size of LTA-type zeolite promotes a filler effect that increases the fluidity of the mortar mixes and they also acts as nucleation sites for the cement hydrates, thus accelerating the cement hydration reactions. This acceleration of the cement hydration promotes the increase of the initial compressive strength of the mortars fabricated with this zeolite type. The higher silica content of NaP-type zeolite promotes pozzolanic reactions that significantly increase the long-term compressive strength of the fabricated mortars.